Towards optimizing prostate tissue retrieval following holmium laser enucleation of the prostate (HoLEP): Assessment of two morcellators and review of literature - Elshal, Ahmed M.; Mekkawy, Ramy; Laymon, Mahmoud; El-Assmy, Ahmed; El-Nahas, Ahmed R. (Canadian Urological Association Journal, 2015)
Introduction: We assess different approaches to retrieve the enucleated adenoma after transurethral enucleation of the prostate, particularly using the holmium laser. Methods: A retrospective review through our prospectively maintained database was performed looking for safety and efficacy of two morcellators. The enucleation phase of the holmium laser enucleation of the prostate (HoLEP) was classically performed followed by retrieval of the intravesical adenoma using either the Piranha (Wolf Inc., Knittlingen, Germany) or VersaCut (Lumenis) morcellator. A PubMed-MEDLINE search was conducted for all transurethral enucleation procedures and relevant data regarding methods of prostate tissue retrieval were extracted. Results: Strictly limiting the study to 3 reusable blades with each morcellator, we performed 67 and 55 consecutive procedures with Piranha and VersaCut, respectively. There was no significant difference between the two morcellators regarding perioperative complications, apart from 5 bladder mucosal injuries with the VersaCut (9%). Furthermore, there were similar retrieved tissue weight, mechanical problems-rate, catheter-time and hospital-stay in both morcellators. However, the Piranha morcellator needed significantly less morcellation-time, needed to use cold loop to remove non-morcellated pieces and to score the adenoma by laser for better bite of the adenoma, and had a higher median morcellation-rate 6.2 (rate: 2.8–12) g/min. Despite little reporting on morcellation, we had data on the tissue retrieval rate (2.6 to 6.5 g/min with Piranha and 1.9 to 11 g/min with VersaCut. Furthermore, bladder mucosal injury was reported in 1.4% and 0.7 to 5.7% with Piranha and VersaCut, respectively; bladder perforation with VersaCut was experienced in about 0.1 to 1.5% of patients. Our study is limited by its non-randomization. Conclusion: The Piranha morcellator was the most efficient and safe way to retrieve tissue after a transurethral enucleation of a prostate adenoma.